Perkembangan Fisik dan Karakteristiknya serta Perkembangan Otak Anak Usia Pendidikan Dasar - Ulfa Kesuma; Khikmatul Istiqomah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2019)
Success in the field of academics in primary schools becomes the main thing as one of the achievements of a student's success, therefore appreciation for those who have high academic ability will be felt. Conversely for those who are in high school, begin to have a paradigm shift towards the meaning of learning success. Student development will go straight with the complexity of the problems faced by the teacher. This study aims to find out how physical development, physical development characteristics and brain development of children of primary education age. This research uses the library research method. The results of this study are the physical development of elementary age children basically influenced by many factors, both internal factors or external factors. The physical development of students will affect the learning process of students, so it is very important for educators to understand the physical development characteristics of their students. In addition to the interests of the teaching and learning process, knowing the physical characteristics of students is also important in terms of approaching students if students experience things that must be helped by educators.